Thraulodes marianoi sp. nov., a remarkable new species of mayfly (Ephemeroptera: Leptophlebiidae) with dark wings from the southern Brazilian Atlantic Forest - de Assis Silva, Vinícius; Salles, Frederico Falcão; Pinto, Ângelo Parise (Zootaxa, 2020)
Thraulodes marianoi sp. nov. is described, illustrated and diagnosed based on a single male imago from a subtropical forest at Pico do Marumbi State Park, in the protected area of Mananciais da Serra, state of Paraná, Brazil. Based on the dark coloration of legs and the large dark spot at base of forewing, T. marianoi sp. nov. is similar to species of the niger-group (Peruvian Amazonia) and to T. basimaculatus Giordano & Domínguez, 2005, a species endemic to Bolivia. The new species can be distinguished from all other species in the genus Thraulodes Ulmer, by the combination of following characteristics: (1) four cross-veins basal to bulla in forewing; (2) brown area covering about of proximal half of the forewing; (3) pleura violet; (4) middle and posterior femora yellowish washed with dark brown; (5) terga and sterna I–IV white washed with dark brown on posterior and lateral margin terga and sterna V–X dark brown; (6) penes short and wide with distolateral area, “ear-like” and poorly developed lateral pouch; (7) styliger plate triangular, median projection short and rounded on the apex. This new species represents the first record of the genus from the state of Paraná, Brazil.